Physiological Characteristics of Wheat Cultivars Treated With Soil Bacteria in a Small-plot Experiment - Láposi, Réka; Dudás, Anna Fruzsina; Tóth, Szilárd Zsolt; Tury, Rita; Bélteki, Ildikó (Journal of Central European Green Innovation, 2025)
This paper presents the results of small-plot field experiment conducted in 2022, a year of severe drought, with soil bacteria-treated wheat cultivars, during which we examined photosynthetic pigments, average yield, and certain quality parameters using in vivo methods. The soil microbe preparation used is especially recommended for use in warn, drought period, and it is also effective for seed treatment. Its use can be expected to result in better nutrient and water supply, more homogeneous stands, and increased stress tolerance. At the beginning of flowering, the SPAD, EVI, RDVI indices, which indicate chlorophyll content in leaves were significantly higher in three varieties (Mv Nemere, Mv Kondás, Mv Pelsodur), while at the same time, these varieties showed higher photochemical activity (PRI), lower stress sensitivity (SIPI), and lower carotenoid content (CRI). Water content was higher in treated individuals for all varieties. For all 8 varieties, the average yield was approximately 10% higher on the treated plots, Mv Nemere. The nutritional values were only of medium quality, but all quality parameters on the treated plots showed better results. The quality parameters indicated only medium quality, but we obtained better results for all quality parameters on the treated plots. Overall, it can be said that the product can be used effectively even in a drought year, but at the higher dose recommended by the manufacturer.
Keywords: wheat cultivars; soil bacteria; photosynthetic pigments; vegetation indices; yield; grain quality